2011
DOI: 10.1111/j.1442-200x.2010.03311.x
|View full text |Cite
|
Sign up to set email alerts
|

Might asphyxia cause respiratory inhibition after crying in mature infants?

Abstract: Damage occurring in utero prior to 36 weeks gestation might cause increased echogenicity or cyst formation in the GE, potentially disturbing maturation of the respiratory center with the development of RIAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…increased echogenicity in the ganglionic eminence [GE], cyst in the GE, or subependymal cyst at the caudothalamic notch) and experience a respiratory pause during feeding (with a decrease in SpO 2 levels to <80%) should be examined for the presence of RIAC. Furthermore, we reported that damage occurring in utero prior to 36 weeks gestation might be the cause of RIAC 3 . In the present study, we evaluated the correlations between changes in cranial ultrasound findings and the presence of RIAC, feeding hypoxemia, and prolonged apnea in preterm infants of less than 34 weeks of gestation, in an effort to clarify the timing of injury in utero resulting in RIAC.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…increased echogenicity in the ganglionic eminence [GE], cyst in the GE, or subependymal cyst at the caudothalamic notch) and experience a respiratory pause during feeding (with a decrease in SpO 2 levels to <80%) should be examined for the presence of RIAC. Furthermore, we reported that damage occurring in utero prior to 36 weeks gestation might be the cause of RIAC 3 . In the present study, we evaluated the correlations between changes in cranial ultrasound findings and the presence of RIAC, feeding hypoxemia, and prolonged apnea in preterm infants of less than 34 weeks of gestation, in an effort to clarify the timing of injury in utero resulting in RIAC.…”
mentioning
confidence: 96%
“…Furthermore, we reported that damage occurring in utero prior to 36 weeks gestation might be the cause of RIAC. 3 In the present study, we evaluated the correlations between changes in cranial ultrasound findings and the presence of RIAC, feeding hypoxemia, and prolonged apnea in preterm infants of less than 34 weeks of gestation, in an effort to clarify the timing of injury in utero resulting in RIAC.…”
mentioning
confidence: 99%